Achieving n-type conduction in YbMg2Sb2-based compounds through defect engineering and doping. (15th January 2022) - Zhou, Ting; Song, Jie; Lei, Xiaobo; Zhang, Qinyong; Bi, Jian; Gao, Daojiang; Jiang, Jing; Wang, Chao
Abstract: Good thermoelectric generators should ideally be realized by utilizing the same compounds in both p-type and n-type materials for achieving high energy conversion efficiency to drive the application. In this work, we enable a conduction transition from p-type to n-type in the YbMg2 Sb2 -based Zintl compounds via Mg vacancies compensation and cation site doping with Y. It is obviously demonstrated that Y is an effective electron donor to realize n-type conduction and increase the carrier concentration. By further Mg-doping in the Yb site, a significantly suppressed lattice thermal conductivity and noticeably enhanced power factor is obtained simultaneously. Thus, n-type YbMg2 Sb2 -based compounds with high power factor, low thermal conductivity, and high figure of merit are obtained. Our work broadens the family of n-type Zintl phase thermoelectric materials, demonstrating that the intrinsic defect chemistry and extrinsic doping are important approaches for such materials systems to achieve n-type conduction. Graphical abstract: Image, graphical abstract